PEMBERDAYAAN BAHASA, SASTRA, DAN AKSARA BALI TERHADAP PENYULUH BAHASA BALI - Ida Ayu Pristina Pidada; Ida Ayu Iran Adhiti; Gede Sidi Artajaya (Widyadari : Jurnal Pendidikan, 2021)
In relation of development, preservation, and developments of Balinese language, literature, and script, the Bali Provincial Culture Services appoints Balinese language instructor contract workers who have competence in the fields of Balinese language, literature, and script. It is intended that people who live in Pakraman village able to understand Balinese languages, literatures, and scripts are properly and correctly. As extension workers, we need personnel who are in accordance with the fields of languages, literatures, and Balinese scripts. Extension workers assigned to Badung Regency are used as samples for languages, literatures, and literacy empowerment because extension workers face complex situations and conditions. The academic team as resource persons provided an in-depth understanding of Balinese language, literatures, and scripts according to their competence as extension workers.